The Role of Private Health Insurance in Creating the Silver Economy in Poland - Laskowska, Iwona (Journal of Finance and Financial Law, 2020)
In the coming decades, Poland will be faced with rapid demographic changes related to the rising proportion of the elderly population. Because of the necessity to sustain economic growth in the new demographic situation, more attention is being given to the so-called silver economy, the significance of which can be considered from social and economic perspectives. The economic value of the silver economy concept lies in highlighting the benefits of unleashing the demand latent in the elderly population. The silver economy has many segments, including insurance focused on risks specific to the elderly. This broad category of insurance also contains private (commercial) health insurance. The paper considers the role of private health insurance in terms of silver economy building in Poland. The research hypothesis verified in the study stated that seniors in Poland can become important investors in the health insurance market. The results of an analysis of seniors’ budgets imply, that an appropriately designed offering might attract interest from this social group.